Chemical and Organoleptic Characteristics of Vegetable Nuggets Based on Oyster Mushrooms and Red Beans - Rahmayuni, Rahmayuni; Ayu, Dewi Fortuna; Septian, Lutfi Dila Dwi (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
Vegetable nuggets are low fat nuggets but have a high protein and fiber content in order to support a vegetarian diet. The purpose of this study was to obtain the best formulation of vegetables nuggets made from oyster mushrooms and red beans in terms of nutritional and sensory characteristics. The research method used a completely randomized design with four treatments and four replications. The treatments consisted of JK1 (95 oyster mushrooms:5 red beans), JK2 (90 oyster mushrooms:10 red beans), JK3 (85 oyster mushrooms:15 red beans), and JK4 (80 oyster mushrooms:20 red beans). The data obtained were statistically analyzed using analysis of variance and continued with Duncan's New Multiple Range Test (DNMRT) at 5% level. The results showed that the combination of oyster mushrooms and red beans significantly affected water, ash, protein, and crude fiber content, as well as descriptive sensory assessments such as color before frying, aroma, elasticity, taste, and overall hedonic assessment. The best treatment was JK4 (80 oyster mushrooms: 20 red beans) which had fulfilled quality requirements of chicken nugget combination (SNI 01-6683-2014) and fish nuggets (SNI 01-7758-2013) with a moisture content of 55.59%, ash content of 1.63%, protein content of 9.49%, and crude fiber content of 4.08%. The overall sensory assessment of the nugget were slightly brown color before frying, yellowness after frying, a little oyster mushroom flavouring before and after frying, a little chewy, and a little red beans taste.